Soft factors in integrating innovation in advanced e-services. (26th May 2011) - Paskaleva, Krassimira; Cooper, Ian; Azorín, José Angel
Along with economic development and competitiveness, contemporary urban destinations are increasingly concerned with improving their services via information and communication technologies (ICT). The latter can be a powerful vehicle for destination promotion, combining positive contributions to the tourism, cultural heritage, visitors' and wider community interests. Based on the results of the ISAAC European project, this paper shows how cultural tourism destinations can develop advanced e-services that improve access and use of their local heritage by adopting innovation practices in integration. It is argued that if these new e-services have to convey diverse, distributed and multi-media information on cultural destinations in order to enrich the user experience and satisfaction then there is a need for wide-ranging innovations – not just technical but also organisational, process and policy – addressing governance and sustainable development issues. The discussion is based on theoretical analysis, previous research conducted by the authors, and three case study examples from Europe – Amsterdam, Leipzig, and Genoa, focusing specifically on the soft factors of innovation and the practical implications of the research reported.